Investigation on structural and optical properties of system Sr2Ce1-xNaxO4 (0.0 ≤ x ≤ 0.10) - Yadav D.; Nirala G.; Kumar U.; Upadhyay S. (My University, 2025)
Powders of a few compositions of the system Sr2Ce1-xNaxO4 (x = 0, 0.02, 0.04, 0.06, and 0.10) have been prepared by the conventional solid-state reaction method. Analysis of the XRD patterns has shown a preference of dopant Na+ for the Sr2+ sites with increasing content of dopant (x). Rietveld refinement of the XRD patterns confirmed that each sample crystallized in orthorhombic structure with space group Pbam. The purity of the synthesized samples was further examined using Raman Fourier Transform Infrared (FTIR) spectroscopy techniques. Raman spectroscopy has further indicated the risk of decomposition of Sr2CeO4 phase with increasing doping concentration. Optical band gap energy computed using UV–visible absorption data (Tauc’s plot) falls between 2.91 and 3.10 eV, decreasing with increasing x. The shape of the excitation and emission spectra remains unchanged with increasing Na+ concentration. Two excitation peaks located around 290 nm and 350 nm are seen in photoluminescence (PL) excitation spectra. All Na-doped samples display an intense blue emission at 472 nm similar to undoped Sr2CeO4. SEM images of fractured surfaces of the sintered pellets have shown a significant role of Na doping on the morphology and grain size of the Sr2CeO4. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.